How firm a foundation [compact disc, unabridged] - Weber, David, 1952- (Weber, David, 1952- Safehold series., 2011)
For five years, Charis has survived all the Church of God Awaiting and the corrupt men who control it have thrown at the island empire. The price has been high and paid in blood. It can hold its own at sea, but if it is to survive, it must defeat the Church upon its own ground. Yet how does it invade the mainland and take the war to a foe whose population outnumbers its own fifteen to one? How does it prevent that massive opponent from rebuilding its fleets and attacking yet again?